System level analysis of a 23GHz transmitter design for point to point microwave link - Rahayu, Yusnita; Din, Jafri; Abdul Rahman, Tharek (2003)
The restricted spectrum frequency and the narrow handwidth allocated by regulatory organizations to wireless users impacts the design of the RF front end. Narrowband amplification and filtering to avoid leakage to adjacent hands is required for transmitter design. Power spectrum of transmitter must not exceed the limits of spectral power density 111. This paper presents a 23GHz transmitter system for point-to-point microwave link. Linearity requirements for the transmitter need to he considered in order to have high power transmit. The system is designed with Advanced Design Software (ADS). A 23 GHz transmitter comprises a double conversion up-converter. The simulation result of power transmit is 21.516 dBm. This is obtained over the 22.999 - 23.549 GHz frequency range. The design of transmitter is the proper choosing and arrangement of microwave components to meet the European Telecommunications Standirds Institute (ETSI) recommendations for point-to-point equipment in fued radio systems operating at 23 GHz.